2000
DOI: 10.1056/nejm200001133420202
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Colonoscopy for the Diagnosis and Treatment of Severe Diverticular Hemorrhage

Abstract: Among patients with severe hematochezia and diverticulosis, at least one fifth have definite diverticular hemorrhage. Colonoscopic treatment of such patients with epinephrine injections, bipolar coagulation, or both may prevent recurrent bleeding and decrease the need for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
571
4
38

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 629 publications
(624 citation statements)
references
References 13 publications
11
571
4
38
Order By: Relevance
“…2 After initial hemodynamic resuscitation, emergent endoscopy is the initial treatment of choice for both acute UGIB 3 and LGIB. [4][5][6] However, the ideal management for ongoing bleeding after failure of endoscopic therapy remains controversial. Acute surgical intervention will eventually be required in 10%-15% of patients, 7 but is associated with a mortality of 25%.…”
mentioning
confidence: 99%
“…2 After initial hemodynamic resuscitation, emergent endoscopy is the initial treatment of choice for both acute UGIB 3 and LGIB. [4][5][6] However, the ideal management for ongoing bleeding after failure of endoscopic therapy remains controversial. Acute surgical intervention will eventually be required in 10%-15% of patients, 7 but is associated with a mortality of 25%.…”
mentioning
confidence: 99%
“…[32]. Every type of endoscopic hemostasis (epinephrine injection and/or bipolar electrocoagulation) was able to prevent early rebleeding [32]. It is also reported that urgent colonoscopy, after adequate colon cleansing and performed by an experienced endoscopist, is able to decrease direct costs and shorten hospital stay in these patients [33,34].…”
Section: Colonoscopy and Diverticular Bleedingmentioning
confidence: 99%
“…For example, Setoyama et al found that endoscopic band ligation was superior to endoscopic clipping in reducing rebleeding rate (p=0.018) [30]. [32]. Every type of endoscopic hemostasis (epinephrine injection and/or bipolar electrocoagulation) was able to prevent early rebleeding [32].…”
Section: Colonoscopy and Diverticular Bleedingmentioning
confidence: 99%
“…Early colonoscopy reduces hospital stay and costs (Strate 2003, Machicado 1997. Therapeutic colonoscopy also reduces the need for surgery (Jensen 2000).…”
Section: Colonoscopymentioning
confidence: 99%